2017
DOI: 10.18683/germs.2017.1110
|View full text |Cite
|
Sign up to set email alerts
|

Enterococcus spp. and S. aureus colonization in neutropenic febrile children with cancer

Abstract: Introduction Febrile neutropenia is one of the most serious treatment-related complications in cancer patients. Susceptible to rapidly progressing infections, which result in prolonged hospitalization and use of broad-spectrum antibiotics, neutropenic patients are subject to colonization by multiresistant agents, which enhances the risk of infections.Methods In this study we included samples collected with nasal, oropharyngeal and anal swabs from hospitalized children with febrile neutropenia following chemoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…During abscess formation, neutrophils are recruited to the site of infection in high numbers. We identified the myeloid cell marker CD14 and neutrophil marker CD177 within the abscess and interface (Figure ). Coinciding with the neutrophil surface markers, multiple neutrophil-specific antimicrobial factors are also found in the abscess and interface regions including myeloperoxidase (Mpo), cathepsin G (Ctsg), and neutrophil elastase (Elane) (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…During abscess formation, neutrophils are recruited to the site of infection in high numbers. We identified the myeloid cell marker CD14 and neutrophil marker CD177 within the abscess and interface (Figure ). Coinciding with the neutrophil surface markers, multiple neutrophil-specific antimicrobial factors are also found in the abscess and interface regions including myeloperoxidase (Mpo), cathepsin G (Ctsg), and neutrophil elastase (Elane) (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…However, after 72 hours, ESBL-producing Klebsiella, Proteus, and Enterococcus were also isolated, which can be attributed to nosocomial colonization. Similarly, CoNS were the most common colonized pathogens in an analysis of 121 nasal, oropharyngeal, and anal swabs taken from children with chemotherapy-related FN by Spinardi et al (15) The second common pathogen was Enterococcus, which may be due to rectal samples.…”
Section: Discussionmentioning
confidence: 94%
“…Colonization with antibiotic-resistant agents can be associated with the increased risk of infection in oncology patients (14). It has been shown that 5% -50% of pediatric oncologic patients who have been colonized will develop bacteremia (15). Colonization with resistant pathogens in oncology patients may indicate a change in the FN management protocol, including antibiotics' empiric administration (16).…”
Section: Introductionmentioning
confidence: 99%
“…In the last two decades, Enterococcus sp. (Spinardi et al, 2017), and treatment difficulties due to their rapid resistance to commonly used antimicrobials such as aminoglycosides, aztreonam, cephalosporins, clindamycin and oxacillin (ANVISA,…”
Section: Introductionmentioning
confidence: 99%